Association between NAG-B and cadmium in urine with no evidence of a threshold. Issue 3 (March 1995) - Bernard, A; Thielemans, N; Roels, H; Lauwerys, R
Abstract : OBJECTIVES–To explore the significance of the increase in urinary excretion of the lysosomal enzyme beta-N-acetylglucosaminidase (NAG) at low exposures to cadmium (Cd) that is frequently found in the absence of any other sign of renal dysfunction. METHODS–The activity was measured of the two main isoenzymes of NAG (NAG-A secreted by exocytosis and NAG-B released with cell membranes) in the urine of 49 male workers employed in a Cd smelter and of 20 age matched controls. RESULTS–An increased urinary excretion of low molecular weight proteins was noted only in subjects who excreted > 10 micrograms Cd/g creatinine. The urinary activity of NAG-B showed a dose related increase that was already significant in the group excreting 0.5-2 micrograms Cd/g creatinine. In multiple regression analysis the NAG-B activity correlated with the excretion of Cd but not with that of lead or mercury. The NAG-A activity was by contrast unaffected by exposure to Cd but correlated with the urinary excretion of lead and copper. CONCLUSIONS–As NAG-B is considered to be the lesional form of NAG, the existence of a specific association between this enzyme and urinary Cd excretion with no detectable threshold suggests that this metal produces cellular alterations at exposures commonly found in the general population.